The role of non-governmental public associations in protecting the rights of persons with disabilities in Ukraine during the war (Law and Safety, 2022)
The problems of persons with disabilities in general and with mental disabilities in particular, which have become even more acute in Ukraine with the beginning of the full-scale armed aggression of the Russian Federation, have been highlighted. The purpose of the study is to determine the role and place of public associations in the process of realizing and protecting the rights of persons with disabilities, in particular persons with mental disabilities (permanent psycho-intellectual disabilities), during the war period, as well as formulating recommendations for improving the state of observance of rights and freedoms this category of persons. The objective impossibility of the population social protection state bodies, which are located in or near the places of hostilities, to perform their functions due to the existing danger for workers, as well as the impossibility of transferring these bodies to a remote work format, has been established.The use of a number of general scientific and special research methods has made it possible to analyzed the situation with respect to the rights of the specified category of persons in Ukraine in current conditions. A significant increase in the role and effectiveness of civil society institutions, in particular non-governmental public associations, has been noted. A conclusion has been made regarding the need to strengthen cooperation between these social service providers. It has been recommended to expand the participation of representatives of such public organizations in the process of making managerial decisions both at the state level and at the level of local self-government.Monitoring and analysis of the dynamics of the effectiveness of both state bodies of social protection of the population and non-state public associations in Ukraine by studying the opinion of the final beneficiaries, such as persons with disabilities, has been defined as a promising direction for further research.
Keywords: human rights; a person with disabilities; state bodies of social protection of the population; mental disability; international standards in the field of rights of persons with disabilities; armed conflict; social services.